Effect of using three types of training (weight-plyometric-compound) for developing muscular ability and the level of performing some defensive skills in handball - Gaber Hassan Abdel Wahab, S. (World Journal of Sport Sciences, 2010)
This research aims at putting three suggested trainings by using (weigh - Plyometric - compound) for the developing the muscle ability and comparing it's effect on the performing some defensive skills in handball, The researcher used the experimental method on a sample of (58) student divided into three groups, eight each and the most important results proud exceed, The third experimental groups which uses the compound training over the first experimental group which used weight training and over the second group which used plyometric in all muscles ability and the level of performing some defensive skills (defensive movements - The block).